Automation and labor demand in European countries: A task-based approach to wage bill decomposition - Martin Lábaj; Matej Vitáloš (University of Economics in Bratislava, Department of Economic Policy, 2019)
To understand the effects of automation and other types of technological changes on European labor demand, we use an empirical decomposition of observed changes in the total wage bill in the economy developed by Acemoglu and Restrepo (2019). The decomposition is derived from a task-based model that allows us to study the effects of different technologies on labor demand. At the center of this framework is the task content of production-measuring the allocation of tasks to factors of production. Automation, by creating a displacement effect, shifts the task content of production against labor, while the introduction of new tasks in which labor has a comparative advantage improves it via the reinstatement effect. Overall effects are country- and time-specific and call for an empirical exploration. We apply the decomposition to 15 European countries with good data coverage in the EU KLEMS database.
Keywords: J23; J24; 330; automation; displacement effect; labor demand; productivity; reinstatement effect; technology; wage share